Navigating Two Worlds: A Netnographic Study of Traditional Healing Integration within Digital Mental Health Communities and Implications for Psychiatric Nursing Practice - Evy Aristawati; Joel Rey Ugsang Acob (Tarqabin Nusantara Group, 2026)
Background: Indonesian mental health service users increasingly negotiate biomedical psychiatric treatment alongside jamu, dukun consultations, and spiritual rituals, yet how this negotiation is enacted and disclosed outside the clinic remains poorly documented. Objective: To examine how Indonesian-language digital communities construct, coordinate, and communicate the integration of traditional healing with psychiatric care, and to derive implications for psychiatric nursing practice. Methods: An 18-week netnographic study (1 February–10 June 2026) of four Indonesian-language digital communities captured 1,563 threads and 9,847 posts from 2,489 participants who explicitly discussed integrating traditional healing with psychiatric treatment. Data were examined using reflexive thematic analysis. Results: Five interconnected themes emerged: epistemological pluralism, concealment and selective disclosure, temporal negotiation patterns, digital knowledge translation, and identity preservation through healing. Most participants (63.0%) concealed traditional healing use from every provider, while digital communities functioned as informal sites of herb–drug interaction surveillance and peer knowledge exchange. Conclusion: Traditional healing integration is better understood as a parallel, patient-managed care system than as covert non-adherence; psychiatric nurses require culturally responsive, non-judgemental assessment approaches that make this system visible rather than punishable